2015
DOI: 10.1002/iid3.71
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia promotes polarization of the immune response in ovalbumin‐induced airway inflammation, leading to a TH17 cell phenotype

Abstract: Previous studies have demonstrated that hyperoxia-induced stress and oxidative damage to the lungs of mice lead to an increase in IL-6, TNF-α, and TGF-β expression. Together, IL-6 and TGF-β have been known to direct T cell differentiation toward the TH17 phenotype. In the current study, we tested the hypothesis that hyperoxia promotes the polarization of T cells to the TH17 cell phenotype in response to ovalbumin-induced acute airway inflammation. Airway inflammation was induced in female BALB/c mice by intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 127 publications
(156 reference statements)
2
16
0
Order By: Relevance
“…This could have important influence on oxidative damage, because neutrophils are a great source of reactive oxygen species [35]. In a previous study, a concomitant elevation of IL-17 levels and neutrophils in the airways induced by hyperoxia were observed [36]. A precursor study showed that hyperoxia-induced inflammatory acute lung injury can be attenuated by inhibition of extracellular HMGB1 [16].…”
Section: Discussionmentioning
confidence: 99%
“…This could have important influence on oxidative damage, because neutrophils are a great source of reactive oxygen species [35]. In a previous study, a concomitant elevation of IL-17 levels and neutrophils in the airways induced by hyperoxia were observed [36]. A precursor study showed that hyperoxia-induced inflammatory acute lung injury can be attenuated by inhibition of extracellular HMGB1 [16].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical hematology is used to evaluate the general state of health of the animal as well as to detect specific diseases [39]. The HG animals had lower serum levels of erythrocytes, hemoglobin, and hematocrit compared to other groups (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of H 2 O 2 possible generates, via Fenton and Haber-Weiss reactions, the hydroxyl radical ( ∙ OH) which can react in the side chain and attacks preferably amino acids such as cysteine, histidine, tryptophan, methionine, and phenylalanine, damaging the proteins and, as its consequence, causing the loss of enzyme activity [47]. Diets with high concentrations of lipids and carbohydrates lead to an increase in free fatty acids (FFAs), resulting in an increase of mitochondrial B-oxidation and the overload in the electron transport chain resulting in an increase of production in ROS [39]. Hyperoxia exposes the body to high levels of reactive oxygen species [5, 6] and the high levels of ROS can inhibit the activity of antioxidant enzymes [48].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used immunohistochemistry to detect the macrophage infiltration on the lung tissue sections. Macrophage phenotype was assessed through immunostaining for iNOS (M1 macrophage marker) and Ym1 (M2 macrophage marker) as hyperoxia increases iNOS expression in macrophages and hyperoxia-exposed murine lungs and inhibits the M2 phenotype in macrophages (39, 40). The rats in the carrier protein + O 2 group significantly exhibited more M1 macrophages than those in the carrier protein + RA or Tn vaccine + RA group.…”
Section: Discussionmentioning
confidence: 99%